HUBUNGAN PROKRASTINASI AKADEMIK DENGAN KECERDASAN SPIRITUAL GENERASI MILENIAL - Yana Dwi Christanti; Rosyida Nurul Anwar (Nurul Jadid University, 2019)
Procrastination that occurs among millennials in the university environment in terms of academic procrastination is due to the mental condition of students. The purpose of this study is to achieve the ultimate goal of educating students who not only become someone who is obedient to religious values, but to meet the spiritual needs of children which includes compassion, security, appreciation, learning, connecting with self-developing, so that they can actualize themselves. The results obtained show the existence of time-limited (delay) and lack of self-control. The delay indicated the occurrence of academic procrastination.